FRI0300 Analysis on the coagulation functional biomarkers and the features of 77 biopsy-proven lupus nephritis patients in southern china. (23rd January 2014) - Jin, O.; Zhang, X.; Fang, L.; Li, Q.; Huang, H.; Wei, Q.; Li, Z.; Liao, Z.; Lin, D.; Gu, J.
Abstract : Objectives: To analyze the coagulation functional biomarkers and the features of 77 biopsy-proven lupus nephritis patients in Southern China. Methods: 77 patients with biopsy-proven lupus nephritis (LN) from Southern China were recruited. There were 66 females (85.7%) and 11 males (14.3%), whose average age were 29.3 ± 10.9 years old. The coagulation functional biomarkers, such as Prothrombin Time (PT), Prothrombin Activity (PTA), Fibrinogen concentration (Fib), Activated Partial Thromboplastin Time (APTT), Thrombin Time (TT), were analyzed according to different pathological LN types. The SLEDAI, 24 hours' urine protein, Blood urea nitrogen (BUN), Serum levels of Creatinine (Scr) Cholesterol (CHOL), Triglyceride (TG), Low density lipoprotein (LDL), Albumin (ALB), Globulin (GLB), complement 3 (C3) and 4 (C4), ESR, CRP and auto-antibodies were evaluated and their correlations to the coagulation functional biomarkers were also analyzed. Results: (1) Renal biopsy revealed type I LN in 12 (15.6%) patients, type II in 12 (15.6%), type III in 4 (5.2%), type IV in 38 (49.4%), type V in 11 (14.3%) patients. (2) The levels of Fib were found ascended in 25 (35.2 %) LN patients, including 2 (16.7%) LN I, 2 (16.7%) LN II, 2 (50%) LN III, 14 (36.8%) LN IV, 5 (45.5%) LN V patients. LN III, IV and V patients were more likely to have increased Fib levels than LN I and LN II patients, though no statistical differences were found. (3) The levels of PTA were found elevated in 28 (26 %) LN patients, including 0 (0%) LN I, 3 (25%) LN II, 2 (50%) LN III, 18 (47.37%) LN IV, 5 (45.5%) LN V patients. The levels of PTA elevated more frequently in LN III, IV, V patients than in LN II patients, and no elevated PTA was found in LN I (p=0.037<0.05). (4) Serum levels of ALB (F=7.45, p<0.001) and C3 (F=4.946, p=0.001) were found differential in different types of LN patients. Levels of ALB were significantly higher in LN I (40.98±1.092) than in LN IV (30.3±1.065, p<0.001) and LN V (33.56±2.477, p=0.008) patients; Levels of C3 in LN I patients (0.95±0.062) were significantly higher than in LN II (0.66±0.094, p=0.02), LN III (0.48±0.174, p= 0.016), LN IV (0.51±0.051, p<0.001) and LN V (0.57±0.089, p=0.004) patients. (5) SLEDAI were found differential in 77 LN patients (F=4.269, p=0.004). The highest were found in type IV LN (17.21±1.029), while LN I (8.50±1.848) was significantly lower than other types (p<0.05); no differences were found between LN II (14.75±2.329), III (15.25±3.497), IV, V (14.00±1.228). (7) Although levels of ALB, C3, SLEDAI were different in 77 patients, no significant correlations were found with those coagulation functional biomarkers (Fib, PTA). Conclusions: (1) The coagulation functional biomarkers (Fib, PTA) are increased more frequently in LN III, IV, V patients than LN I and II patients, indicates LN III, IV, V patients may have more coagulation problems. (2) LN IV patients have more elevated Fib and PTA levels, the highest SLEDAI, the lowest levels of ALB and C3, while the LN I patients have the normal coagulation function, the lowest SLEDAI, the highest levels of ALB and C3. Disclosure of Interest : None Declared